Transplacental transfer of measles and total IgG. - Gonçalves, G. (Cambridge University Press, 1999)
This study was conducted to evaluate factors affecting the levels of total IgG (tIgG) and measles specific IgG (mIgG) in mother and cord sera, and the efficiency of transplacental transport of tIgG and mIgG. The study was conducted in four hospitals in Oporto, Portugal, where 1539 women and their newborns were enrolled. Measles IgG levels were lower among vaccinated mothers and respective cord sera than among vaccinated counterparts. Cord mIgG was strongly correlated with maternal levels in both vaccinated and unvaccinated groups. Transplacental transport efficiency (TTE) of mIgG decreased with increasing maternal levels, although almost one third of the observed effect was due to measurement error. The TTE was not affected by vaccination status. Monitoring maternal measles antibody levels and maternal vaccination status could be useful to determine when the age for measles vaccination can be reduced.